Integrating a blended discovery learning model with a bioenial website to empower science process skills and scientific attitude - Fauziyah Almaas, Ainanur; Harlita, Harlita; Sugiharto, Bowo (Biosfer: Jurnal Pendidikan Biologi, 2024)
This study aims to determine; 1) the effect of integrating blended discovery learning with a bioenial website to empower Science Process Skills (SPS) of grade X students on the material of environmental change and preservation and 2) the effect of integrating blended discovery learning with a bioenial website to empower the scientific attitude of grade X students on the material of environmental change. The research method used a quasi experiment with a quantitative approach. The research design used posttest only control group design to measure SPS and pretest-posttest nonequivalent control group design to measure scientific attitudes. The population in this study were X grade students of SMA Negeri A Sukoharjon the 2022/2023 academic year. The samples of this study were X2 class as experimental class 1 as many as 36 students, X4 as experimental class 2 as many as 36 students, and X5 as control class as many as 36 students. The sampling technique used was cluster random sampling. Data collection questionnaire (scientific attitude), observation (SPS, scientific attitude, syntax implementation), and documentation. Data analysis technique used ANOVA hypothesis test for SPS and ANCOVA for scientific attitude. The ANOVA test results showed the effect of integrating blended discovery learning with the bioenial website to empower SPS. The results of further testing with LSD show that Blended Discovery Learning is a treatment that is significantly different among the three class groups. The ANCOVA test results show that there is no effect of integrating blended discovery learning with the bioenial website to empower scientific attitudes